PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MENGGUNAKAN SMART APPS CREATOR UNTUK KETERAMPILAN MENYIMAK DI KELAS IV SDN 05 KOTO BARU - Lika Apreasta; Martiya Nurni Khairita; Era Susmika (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to produce interactive learning media development products using smart apps creator in chapter VIII material, I am a healthy child in class IV. This research uses the type of research and development. This 4D (four-D) development model has four stages, namely: definition, design, development and dissemination. The type of data taken is from the development of interactive learning media, namely quantitative and qualitative. The instruments used in this research are validation of interactive learning media, instruments for the practicality of interactive learning media, instruments for the effectiveness of interactive learning media, data collection techniques used are interviews, observation and questionnaires. The results of research on interactive learning media using smart apps creators resulted in content, material and language validation scores with an average score of 92.06% categorized as very valid. The practicality of interactive learning media using smart apps creator received a score of 89.52% which was categorized as very valid. The effectiveness of interactive learning media using smart apps creator obtained a score of 91.30%, categorized as very effective.